Stress Studies of Tenofovir Disoproxil Fumarate by HPTLC in Bulk Drug and Pharmaceutical Formulation - Shweta Havele; Sunil R. Dhaneshwar (The Scientific World Journal)
A stability-indicating high-performance thin-layer chromatographic (HPTLC) method for determination of tenofovir disoproxil fumarate in bulk drug and in tablet has been developed and validated. The mobile phase selected was chloroform : methanol (9.0 : 1.0, v/v) with ultraviolet (UV) detection at 260 nm. The retention factor was found to be 0.49 ± 0.03 with correlation coefficients of 0.9994 in the range 300–1500 ng/spot and with an accuracy of 99.25%. Method had the potential to determine tenofovir disoproxil fumarate from tablet without any interference, and it was a stability-indicating one.